Usability Evaluation Aplikasi Berbasis Website dengan Menggunakan Metode Importance Performance Analysis - Fajar Alam, Putra; Wulandari, Sari (Universitas Diponegoro, 2020)
The Ministry of Environment and Forestry provides an appeal to waste banks to use online systems in managing waste bank activities. The online system referred to is the online waste management system through the banksampah.id account. However, the level of activity of garbage banks in using the online system is relatively low (36.46%). Besides, in 2019, the Bandung City DLH has used banksampah.id as an application in evaluating the performance of waste banks. Therefore, this study was conducted aiming to evaluate the level of usability of banksampah.id so that it can be known aspects of banksampah.id that need to be improved. Evaluation of usability level is carried out using the Importance Performance Analysis (IPA) method. The usability evaluation results show that there are 7 usability attributes in the